2020
DOI: 10.4103/ijmr.ijmr_2539_19
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric validation of indigenous molecular test Truenat™ MTB for detection of Mycobacterium tuberculosis in sputum samples from presumptive pulmonary tuberculosis patients in comparison with reference standards

Abstract: Background & objectives: Early case detection is essential to interrupt transmission and to prevent further spread of tuberculosis (TB) in high endemic settings. Nucleic acid amplification tests (NAATs) with visual read-outs are ideal as point-of-care tests. Truenat™ MTB is an indigenous chip-based NAAT for detection of Mycobacterium tuberculosis , which involves extraction of DNA and real-time polymerase chain reaction (PCR) using portable, automated, battery-operated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…The current study demonstrated lower sensitivity but comparable specificity in children as compared to earlier studies in adults, Truenat MTB-RIF Dx demonstrated sensitivity and specificity of 88.3% and 73.8% for detection of MTB in adults 2 . The sensitivity and specificity for detection of Rif resistance in one study was 87.5% and 99.5% respectively 9 .…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The current study demonstrated lower sensitivity but comparable specificity in children as compared to earlier studies in adults, Truenat MTB-RIF Dx demonstrated sensitivity and specificity of 88.3% and 73.8% for detection of MTB in adults 2 . The sensitivity and specificity for detection of Rif resistance in one study was 87.5% and 99.5% respectively 9 .…”
Section: Discussioncontrasting
confidence: 49%
“…However, GeneXpert requires a highly sophisticated laboratory with ambient temperature between 15 and 30 °C, stable electricity supply, and adequate storage space for the cartridges (storage at 2–28 °C), thereby, limiting its use to district hospital settings. Certain newer NAATs have shown promise in studies done in older patients 2 . MolBio Diagnostics (Goa, India) developed three different assays namely Truenat MTB, Truenat MTB Plus and Truenat MTB-RIF Dx based on chip-based real-time Polymerase Chain Reaction (PCR) that utilizes nrdB gene (Truenat MTB), nrdz and IS6110 gene (Truenat MTB Plus) for the semi-quantitative detection of Mycobacterium tuberculosis (MTB) and rpoB gene (Truenat MTB-RIF Dx) for the detection of rifampicin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Our study documented comparable Truenat sensitivity done on the same sample under primary health care to that documented in a multicenter diagnostic accuracy study [ 7 ]. However, slightly lower sensitivity of Truenat MTB Plus has been documented compared to other previous studies [ 8 , 9 ] possibly and partly attributed to the fact that these studies analyzed two sputum samples rather than one spot sample in our study, which is routinely done in Uganda, and were largely not done in primary health care centers. In addition, these previous studies had a different composition of smear negative but culture positive individuals than in our study.…”
Section: Discussionmentioning
confidence: 53%
“…In 2020, a new molecular TB diagnostic tool named Truenat (MTB, MTB Plus, and MTB-RIF) was developed by Molbio Diagnostics, Bangalore, India for the detection of TB and RIF-resistance from sputum samples within an hour, and Truenat MTB identified more positives among culture-confirmed samples than Xpert and had higher sensitivity. 25…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, a new molecular TB diagnostic tool named Truenat (MTB, MTB Plus, and MTB-RIF) was developed by Molbio Diagnostics, Bangalore, India for the detection of TB and RIF-resistance from sputum samples within an hour, and Truenat MTB identified more positives among culture-confirmed samples than Xpert and had higher sensitivity. 25 Despite all these technologies being in place for several years, their reported uptake in high TB burden countries remains low and the factors influencing their uptake are unknown. Our study aimed at documenting the status of the uptake and PEN factors influencing the uptake of WHOendorsed TB diagnostic technologies in the 47 member states of WHO/AFR considering TB diagnostic technologies endorsed by WHO between 2007-2021.…”
Section: Introductionmentioning
confidence: 99%